2020
DOI: 10.1111/jdi.13205
|View full text |Cite
|
Sign up to set email alerts
|

Failure to confirm a sodium–glucose cotransporter 2 inhibitor‐induced hematopoietic effect in non‐diabetic rats with renal anemia

Abstract: Aims/Introduction: Clinical studies have shown that treatment with inhibitors of sodium-glucose cotransporter 2 (SGLT2) significantly increases the hematocrit in patients with type 2 diabetes. To investigate whether SGLT2 inhibitors directly promote erythropoietin production independently on blood glucose reduction, the hematopoietic effect of the specific SGLT2 inhibitor, luseogliflozin, was examined in non-diabetic rats with renal anemia. Materials and Methods: Renal anemia was induced by treatment with aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…This decrease was associated with a decreased GFR and increased blood erythropoietin expression and erythrocyte reticulocyte count. In contrast, no such changes were observed in other studies ( 31 , 32 ). Therefore, these data suggest that the effects of SGLT2 inhibitors in promoting erythropoietin production in the kidney differ depending on the pathogenesis of CKD.…”
Section: Sglt2 Inhibitor-induced Changes In Renal Hemodynamics and Th...contrasting
confidence: 74%
“…This decrease was associated with a decreased GFR and increased blood erythropoietin expression and erythrocyte reticulocyte count. In contrast, no such changes were observed in other studies ( 31 , 32 ). Therefore, these data suggest that the effects of SGLT2 inhibitors in promoting erythropoietin production in the kidney differ depending on the pathogenesis of CKD.…”
Section: Sglt2 Inhibitor-induced Changes In Renal Hemodynamics and Th...contrasting
confidence: 74%
“…Given this overwhelming evidence, it is surprising that data from preclinical studies in rodents with non-diabetic renal damage, which are inevitable to identify the mechanistic background behind nephroprotection, have so far provided rather inconsistent results. A number of in vivo studies reported no improvement of renal impairment by SGLT2 inhibitors caused by, e.g., 5/6 nephrectomy in rats (Zhang et al, 2016;Rajasekeran et al, 2018), polycystic kidney disease in rats (Kapoor et al, 2015), oxalate-induced nephrocalcinosis in mice (Ma et al, 2017) and adenine-induced fibrosis in rats (Yamazaki et al, 2020). On the contrary, data supporting a renal benefit by SGLT2 inhibition were provided from disease models like ischemia-reperfusion injury (Chang et al, 2016), unilateral ureteric obstruction (Abbas et al, 2018), proteinoverload proteinuria (Cassis et al, 2018), Ang II-dependent hypertension (Castoldi et al, 2020), cyclosporine-A nephropathy (Castoldi et al, 2021), adenine nephropathy (Yamato et al, 2020) and salt-sensitive hypertension in uninephrectomized rats (Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in Hb levels is also observed in patients with impaired renal function, which may be related to the renoprotective effect of SGLT2 inhibitors. Yamazaki Wistar rats (male, 5 weeks old) and investigated its anemia suppression effects (24). No increase in Hb and Hct levels was observed in renal anemia.…”
Section: Discussionmentioning
confidence: 99%